Robust TDOA Localization Algorithm for Asynchronous Wireless Sensor Networks - Hui Xiong; Zhiyuan Chen; Wei An; Beiya Yang (International Journal of Distributed Sensor Networks)
This paper presents a tag localization algorithm based on the time-difference-of-arrival (TDOA) of mobile tag signal for asynchronous wireless sensor network (WSN) with N anchors (nodes with known locations) and a large number of mobile tags. To obtain time synchronization, all anchors broadcast signals periodically; relative clock offsets and skews of anchor pairs are estimated by the least-square (LS) method using the times-of-arrival (TOAs) of broadcast signals at anchors. When a tag transmits signal, the TOA of tag signal at each anchor is stamped and errors in original TDOAs of tag signal due to relative clock offsets and skews of anchor pairs are eliminated. Based on Gaussian noise model, maximum likelihood estimation (MLE) for the tag position is obtained. Performance issues are addressed by evaluating the Cramér-Rao lower bound of synchronization and localization algorithms. Since the tag can be located via a single transmission, least power consumption of tag is required, and large number of tags can be served in WSN. The proposed algorithm is simple and effective, with performance close to that of synchronous TDOA algorithm.